Impact of Trade Show Marketing Activities on Customer Engagement : A B2B Perspective - Kapoor, Mansi; Joshi, Rakesh Mohan (Indian Journal of Marketing, 2024)
Purpose : This study aimed to create and test a methodology to investigate the impact that trade show organizers’ recurring pre-show, at-show, and post-show marketing activities have on increasing exhibitor engagement at the show. Trade show planners need to create well-planned events with well-considered marketing strategies to increase attendance if they want to stand out in a competitive industry. Design/Methodology/Approach : The study examined a range of three-phase trade show marketing initiatives, including pre-show, at-show, and post-show, that trade show organizers regularly carry out to increase exhibitor participation. This study tested the customer engagement model empirically and validated a 46-item scale that included 10 variables. The model of trade show marketing activities with customer involvement was tested in this study using structural equation modeling and quantitative research techniques. Data from 349 exhibitors at multi-sector trade exhibitions was gathered. The model of trade show marketing activities on exhibitor engagement was tested using SEM as a quantitative research tool, drawing on trade show literature. This goal was accomplished with the use of quantitative surveys that apply correlation and SEM analysis between marketing efforts and customer participation in trade fairs, utilizing the questionnaire method as a data-gathering instrument. Data from 349 exhibitors at multi-sector trade exhibitions was gathered. Findings : The results demonstrated how trade shows were essentially used as a channel for marketing communications to raise customer involvement. Thus, the organizer needs to comprehend what exhibitors deem successful in a trade show and how trade show marketing initiatives might boost exhibitor engagement. The success of a trade show is greatly impacted by the exhibitors’ involvement and active participation; thus, organizers must properly engage them. Practical Implications : Practitioners could leverage the insights by developing comprehensive marketing plans that encompass pre-show promotion, engaging activities during the event, and follow-up initiatives post-show. Organizations may enhance trade show performance metrics and optimize client interaction by implementing a comprehensive trade show marketing strategy. Originality/Value : The paucity of research and the literature’s lack of attention on trade show organizers rather than exhibitors account for the paper’s novel contribution. The research closed this knowledge gap by understanding the dynamic influence of the three stages of marketing activities on different engagement qualities.